Molecular drivers of cellular metabolic reprogramming in melanoma. Issue 3 (March 2015) - Abildgaard, Cecilie; Guldberg, Per
Highlights Profound changes in cellular metabolism are a hallmark of melanoma. Rewiring of metabolism is controlled by known melanoma drivers. Metabolic changes in melanoma represent new targets for therapeutic intervention. Treatment effectiveness may depend on genetic drivers and mitochondrial performance.